(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current knowledge and preventive practices regarding hand foot mouth disease among mothers with children under five years old in Vinh Thanh commune, Ca Mau province, in 2025. Methods: A cross-sectional study was conducted among mothers with children under five residing in Vinh Thanh commune, Ca Mau province. Results: The study results showed that the population had a certain level of general knowledge about hand foot mouth disease; however, detailed knowledge and preventive practices remained limited; only 28% achieved satisfactory knowledge and 24.9% demonstrated proper preventive practices. Mothers with good knowledge were 2.1 times more likely to practice correct prevention measures (p < 0.05), indicating a significant association between knowledge and behavior. Conclusion: The study shows that mothers in Vinh Thanh commune have limited knowledge and practices regarding hand foot mouth disease, with only 28% achieving adequate knowledge and 24.9% demonstrating correct practices; in particular, regular handwashing with soap is not well maintained. Better knowledge increases the likelihood of correct practices by 2.1 times. Therefore, strengthening health communication and periodic training is necessary to improve mothers’ understanding and enhance preventive hygiene behaviors within the community.